Zinc selenide composite carbon material, electrochemical device and electronic equipment
By using a zinc selenide composite carbon material connected by a porous carbon substrate and zinc selenide nanoparticles through Zn-O-C bond in a sodium ion battery, the problems of large volume expansion effect and poor circulation performance of the negative electrode material in the prior art are solved, and the problem of High magnification and high cycling performance of the battery.
Patent Information
- Application Number
- CN202411577983.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
The existing transition metal negative electrode materials have problems such as large volume expansion effects and poor circulation performance in sodium ion batteries, and it is difficult to take into account both high rate performance and high circulation performance.
The porous carbon substrate is used to connect the zinc selenide nanoparticles through the Zn-O-C bond to form zinc selenide nanoparticles anchored on the porous carbon substrate, thereby building a fast channel to improve ion and electron transport efficiency.
The excellent rate performance and cycle performance of electrochemical devices in sodium ion batteries are achieved, and the cycle life of the battery is extended.
Smart Images

Figure CN119447243A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a zinc selenide composite carbon material, an electrochemical device and an electronic device. Background Art
[0002] As a new option for low-cost energy storage, sodium-ion batteries are receiving more and more attention from the market and are very likely to become a substitute for LFP energy storage in the future.
[0003] The existing transition metal negative electrodes have a huge volume expansion effect and poor cycle performance. Therefore, it is of great application value and prospect to develop a negative electrode material that can reduce volume expansion, improve cycle life and rate performance. Summary of the invention
[0004] In order to solve the defect that the prior art cannot take into account both high rate performance and high cycle performance, the present invention provides a zinc selenide composite carbon material, an electrochemical device and an electronic device. The electrochemical device containing the zinc selenide composite carbon material of the present invention can have excellent rate performance and cycle performance at the same time.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] In a first aspect, the present invention provides a zinc selenide composite carbon material, which includes a porous carbon substrate and zinc selenide nanoparticles, wherein the porous carbon substrate and the zinc selenide nanoparticles are connected by Zn-OC bonds to form the zinc selenide nanoparticles anchored on the porous carbon substrate.
[0007] In a second aspect, the present invention provides an electrochemical device, wherein the negative electrode sheet of the electrochemical device comprises the zinc selenide composite carbon material as described above.
[0008] In a third aspect, the present invention provides an electronic device comprising the electrochemical device as described above.
[0009] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0010] The reagents and raw materials used in the present invention are commercially available.
[0011] The positive and progressive effects of the present invention are:
[0012] The present invention connects the porous carbon substrate and zinc selenide nanoparticles with a Zn-OC bond, thereby constructing a fast channel that is beneficial to the transmission of ions and electrons. At the same time, the amount of active sites of the zinc selenide composite carbon material and the efficiency of lithium ion binding with the zinc selenide composite carbon material are increased, which is also beneficial to the rapid transmission of ions. Therefore, when the zinc selenide composite carbon material of the present invention is used in an electrochemical device, the electrochemical device has excellent rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a nitrogen adsorption / desorption isotherm curve of the zinc selenide composite carbon material of Example 1.
[0014] Figure 2 This is the pore size distribution diagram of the zinc selenide composite carbon material of Example 1.
[0015] Figure 3 This is the TG / DTA diagram of the zinc selenide composite carbon material of Example 1.
[0016] Figure 4 This is a SEM image of the zinc selenide composite carbon material of Example 1, magnified 2000 times.
[0017] Figure 5 This is a SEM image of the zinc selenide composite carbon material of Example 1, magnified 5000 times.
[0018] Figure 6 This is a SEM image of the zinc selenide composite carbon material of Example 1, magnified 10,000 times.
[0019] Figure 7 This is a mapping image of the zinc selenide composite carbon material of Example 1.
[0020] Figure 8 This is the TEM image of the zinc selenide composite carbon material of Example 1.
[0021] Fig. 9 This is the HRTEM image of the zinc selenide composite carbon material of Example 1.
[0022] Fig.10 This is the SAED pattern of the zinc selenide composite carbon material of Example 1.
[0023] Fig.11 XRD spectra of the zinc selenide composite carbon material (ZnSe / C) of Example 1, zinc selenide (pure ZnSe) and pure carbon (Carban) of Comparative Example 1.
[0024] Fig.12 This is the Raman spectrum of Example 1.
[0025] Fig.13The infrared spectra of the zinc selenide composite carbon material (ZnSe / C) of Example 1, the zinc selenide (ZnSe) of Comparative Example 1, pure carbon (Carban) and zinc acetylacetonate (Zine acetylacetonate).
[0026] Fig.14 This is the full XPS spectrum of the zinc selenide composite carbon material of Example 1.
[0027] Fig.15 This is a high-resolution spectrum diagram of C1s of the XPS spectrum of the zinc selenide composite carbon material of Example 1.
[0028] Fig.16 This is a high-resolution spectrum diagram of O1s of the XPS spectrum of the zinc selenide composite carbon material of Example 1.
[0029] Fig.17 This is a high-resolution spectrum diagram of Zn 2p in the XPS spectrum of the zinc selenide composite carbon material of Example 1.
[0030] Fig.18 This is a high-resolution spectrum of Se 3d in the XPS spectrum of the zinc selenide composite carbon material of Example 1.
[0031] Fig.19 This is a TEM image of the zinc selenide composite carbon material prepared from the zinc selenide composite carbon material in Example 1 after the battery has been cycled 500 times.
[0032] Fig. 20 This is a HRTEM image of the zinc selenide composite carbon material prepared from the zinc selenide composite carbon material in Example 1 after the battery has been cycled 500 times.
[0033] Fig.21 This is the SAED diagram of the zinc selenide composite carbon material prepared from the zinc selenide composite carbon material in Example 1 after the battery has been cycled 500 times.
[0034] Fig. 22 This is the non-in-situ XRD pattern of the zinc selenide composite carbon material of Example 1 under different charge and discharge pressures.
[0035] Fig.23 for Fig. 22 The corresponding charge and discharge curves.
[0036] Fig.24 It is a cycle performance diagram of the zinc selenide composite carbon material (ZnSe / C) of Example 1, the zinc selenide (Bulk ZnSe) of Comparative Example 1, and pure carbon (Carban).
[0037] Fig.25 This is a constant current discharge / charge curve of the zinc selenide composite carbon material (ZnSe / C) of Example 1 at 0.5 A / g.
[0038] Fig.26 Graph showing the rated capacity of the zinc selenide composite carbon material (ZnSe / C) of Example 1 and the zinc selenide (pure ZnSe) of Comparative Example 1 at different current densities.
[0039] Fig. 27 This is the discharge / charge platform diagram of the zinc selenide composite carbon material (ZnSe / C) of Example 1.
[0040] Fig.28 Schematic diagram of the long cycle stability of the zinc selenide composite carbon material (ZnSe / C) of Example 1 at a high current density of 5A / g.
[0041] Fig.29 Schematic diagram of the preparation steps of the zinc selenide composite carbon material of Example 35. DETAILED DESCRIPTION
[0042] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0043] Zinc selenide composite carbon material
[0044] In the zinc selenide composite carbon material provided in the first aspect of the present invention, it includes a porous carbon substrate and zinc selenide nanoparticles, and the porous carbon substrate and the zinc selenide nanoparticles are connected by Zn-OC bonds to form the zinc selenide nanoparticles (SeZn-OC) anchored on the porous carbon substrate.
[0045] The inventors have found that in zinc selenide composite carbon materials, zinc selenide nanoparticles can be anchored on a porous carbon substrate through the action of the Zn-OC bond, and the Zn-OC bond can construct a fast channel that is conducive to the transmission of ions and electrons; at the same time, the porous structure of the porous carbon substrate increases the specific surface area of the material, increases the active sites, and is also conducive to the rapid transmission of ions.
[0046] In certain preferred embodiments of the present invention, the porosity of the zinc selenide composite carbon material is 20%-45%.
[0047] In some specific embodiments of the present invention, the porosity of the zinc selenide composite carbon material is 15%-50%.
[0048] In some specific embodiments of the present invention, the porosity of the zinc selenide composite carbon material is 20%-45%.
[0049] In some specific embodiments of the present invention, the porosity of the zinc selenide composite carbon material is 21%-37%.
[0050] In some specific embodiments of the present invention, the porosity of the zinc selenide composite carbon material is 16%, 18%, 21%, 26%, 27%, 28%, 29%, 32%, 34%, 36%, 37%, 38%, 39%, 40%, 42%, 45% or 46%.
[0051] In certain preferred embodiments of the present invention, the pore volume of the zinc selenide composite carbon material is 0.001-0.02 cm 3 / g.
[0052] In some specific embodiments of the present invention, the pore volume of the zinc selenide composite carbon material is 0.0017-0.0067cm 3 / g.
[0053] In some specific embodiments of the present invention, the pore volume of the zinc selenide composite carbon material is 0.003-0.007 cm 3 / g.
[0054] In some specific embodiments of the present invention, the pore volume of the zinc selenide composite carbon material is 0.001 cm 3 / g, 0.0012cm 3 / g, 0.0017cm 3 / g, 0.0018cm 3 / g, 0.0019cm 3 / g, 0.0023cm 3 / g, 0.0025cm 3 / g, 0.0031cm 3 / g, 0.0036cm 3 / g, 0.0037cm 3 / g, 0.0039cm 3 / g, 0.004cm 3 / g, 0.0041cm 3 / g, 0.0043cm 3 / g, 0.0046cm 3 / g, 0.0047cm 3 / g, 0.0048cm 3 / g, 0.0052cm 3 / g, 0.0053cm 3 / g, 0.0054cm 3 / g, 0.0057cm 3 / g, 0.0059cm 3 / g, 0.0061cm3 / g, 0.0067cm 3 / g or 0.0086cm 3 / g.
[0055] In certain preferred embodiments of the present invention, the average pore diameter of the zinc selenide composite carbon material is 30-50 nm.
[0056] In some specific embodiments of the present invention, the average pore size of the zinc selenide composite carbon material is 20-50 nm.
[0057] In some specific embodiments of the present invention, the average pore diameter of the zinc selenide composite carbon material is 35-45 nm.
[0058] In some specific embodiments of the present invention, the average pore diameter of the zinc selenide composite carbon material is 38-43 nm.
[0059] In some specific embodiments of the present invention, the average pore size of the zinc selenide composite carbon material is 22nm, 25nm, 26nm, 28nm, 30nm, 31nm, 32nm, 34nm, 36nm, 37nm, 38nm, 40nm, 43nm, 44nm, 45nm or 48nm.
[0060] In certain preferred embodiments of the present invention, the specific surface area of the zinc selenide composite carbon material is 5-10 m 2 / g.
[0061] In some specific embodiments of the present invention, the specific surface area of the zinc selenide composite carbon material is 3-10 m 2 / g.
[0062] In some specific embodiments of the present invention, the specific surface area of the zinc selenide composite carbon material is 5.2-8.7 m 2 / g.
[0063] In some specific embodiments of the present invention, the specific surface area of the zinc selenide composite carbon material is 6.1-6.9 m 2 / g.
[0064] In some specific embodiments of the present invention, the specific surface area of the zinc selenide composite carbon material is 3.56m 2 / g、 3.79m 2 / g、5.22m 2 / g、5.28m 2 / g、5.32m 2 / g、5.76m 2 / g、5.99m 2 / g、 6.18m 2 / g, 6.27m 2 / g, 6.33m 2 / g, 6.64m 2 / g, 6.73m 2 / g, 6.77m 2 / g, 6.78m 2 / g, 6.79m 2 / g, 6.81m 2 / g, 6.82m 2 / g, 7.16m 2 / g, 7.36m 2 / g, 7.51m 2 / g, 7.59m 2 / g, 7.83m 2 / g, 8.03m 2 / g, 8.39m 2 / g, 8.63m 2 / g or 8.69m 2 / g.
[0065] In certain preferred embodiments of the present invention, the particle size D50 of the zinc selenide nanoparticles is ≤100 nm.
[0066] In certain preferred embodiments of the present invention, the particle size D50 of the zinc selenide nanoparticles is 10-40 nm.
[0067] In some specific embodiments of the present invention, the particle size D50 of the zinc selenide nanoparticles is 20-35 nm.
[0068] In some specific embodiments of the present invention, the particle size D50 of the zinc selenide nanoparticles is 25-30 nm.
[0069] In some specific embodiments of the present invention, the particle size D50 of the zinc selenide nanoparticles is 21 nm, 22 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 35 nm, 38 nm, 44 nm, 83 nm or 85 nm.
[0070] In certain preferred embodiments of the present invention, the mass content of the porous carbon substrate in the zinc selenide composite carbon material is 15%-40%, wherein % means the mass percentage of the porous carbon substrate in the zinc selenide composite carbon material.
[0071] In some specific embodiments of the present invention, the mass content of the porous carbon substrate in the zinc selenide composite carbon material is 2%-40%.
[0072] In some specific embodiments of the present invention, the mass content of the porous carbon substrate in the zinc selenide composite carbon material is 15%-30%.
[0073] In some specific embodiments of the present invention, the mass content of the porous carbon substrate in the zinc selenide composite carbon material is 20%-30%.
[0074] In some specific embodiments of the present invention, the mass content of the porous carbon substrate in the zinc selenide composite carbon material is 2%, 11%, 12%, 15%, 20%, 24%, 25%, 28%, 30%, 31%, 32%, 33%, 34%, 36%, 37% or 40%.
[0075] In certain preferred embodiments of the present invention, the mass content of the zinc selenide nanoparticles in the zinc selenide carbon composite material is 60%-85%, wherein % means the mass percentage of the zinc selenide nanoparticles in the zinc selenide carbon composite material.
[0076] In some specific embodiments of the present invention, the mass content of the zinc selenide nanoparticles in the zinc selenide composite carbon material is 60%-98%.
[0077] In some specific embodiments of the present invention, the mass content of the zinc selenide nanoparticles in the zinc selenide composite carbon material is 70%-85%.
[0078] In some specific embodiments of the present invention, the mass content of the zinc selenide nanoparticles in the zinc selenide composite carbon material is 75%-85%.
[0079] In some specific embodiments of the present invention, the mass content of the zinc selenide nanoparticles in the zinc selenide composite carbon material is 60%, 63%, 65%, 66%, 67%, 68%, 69%, 70%, 72%, 75%, 76%, 80%, 85%, 88%, 89% or 98%.
[0080] In certain embodiments of the present invention, the porous carbon substrate comprises amorphous carbon.
[0081] In some other specific embodiments of the present invention, the porous carbon substrate comprises amorphous carbon and / or graphitized carbon.
[0082] In certain preferred embodiments of the present invention, the mass content of oxygen in the zinc selenide composite carbon material is 5%-20%. Wherein, % means the mass of oxygen as a percentage of the mass of the zinc selenide composite carbon material. Wherein, the mass content of oxygen in the zinc selenide composite carbon material is used to reflect the content of Zn-OC bonds in the zinc selenide composite carbon material. The higher the mass content of oxygen in the zinc selenide composite carbon material, the higher the content of Zn-OC bonds.
[0083] In certain specific embodiments of the present invention, the mass content of oxygen in the zinc selenide composite carbon material is 0.1%-20%.
[0084] In a specific embodiment of the present invention, the mass content of oxygen in the zinc selenide composite carbon material is 1%-25%.
[0085] In a specific embodiment of the present invention, the mass content of oxygen in the zinc selenide composite carbon material is 8%-16%.
[0086] In a specific embodiment of the present invention, the mass content of oxygen in the zinc selenide composite carbon material is 8%-13%.
[0087] In a specific embodiment of the present invention, the mass content of oxygen in the zinc selenide composite carbon material is 0.1%, 0.17%, 1%, 3%, 5%, 5.5%, 6%, 8%, 9%, 10%, 12.5%, 14%, 16%, 17%, 18%, 18.5% or 24%.
[0088] Preparation method of zinc selenide composite carbon material
[0089] In certain specific embodiments of the present invention, the method for preparing the zinc selenide composite carbon material comprises the following steps:
[0090] calcining the raw material mixture in an atmosphere containing H2;
[0091] Wherein, the raw material mixture comprises a selenium source, a zinc source and a carbon source containing a carboxyl group; or, the raw material mixture comprises a selenium source and a carbon source containing a carboxyl zinc coordination bond.
[0092] The carbon source containing carboxyl zinc coordination bonds in the present invention means: a carbon source containing coordination bonds between carboxyl groups and zinc ions.
[0093] In some specific embodiments of the present invention, the carboxyl-containing carbon source is one or more of carboxylic acid, carboxylated carbon nanotubes and graphite oxide.
[0094] In some specific embodiments of the present invention, the zinc source is zinc nitrate.
[0095] In some specific embodiments of the present invention, the selenium source is elemental selenium.
[0096] In some specific embodiments of the present invention, the mass ratio of the zinc source, the carboxyl-containing carbon source and the selenium source is (1.5-2.5):1:(1.5-2.5).
[0097] In some specific embodiments of the present invention, the mass ratio of the zinc source, the carboxyl-containing carbon source and the selenium source is 2:1:2, 1.5:1:2, 2.5:1:2, 1:1:2, 3:1:2, 2:1:1.5, 2:1:2.5, 2:1:1 or 2:1:3.
[0098] In some specific embodiments of the present invention, the volume concentration of H2 in the H2-containing atmosphere is 5%-20%.
[0099] In some specific embodiments of the present invention, the volume concentration of H2 in the H2-containing atmosphere is 3%, 5%, 10%, 20% or 30%.
[0100] In some specific embodiments of the present invention, the mass content of carboxyl groups in the carboxyl-containing carbon source is 0.5%-70%, wherein % means the percentage of the mass of carboxyl groups to the mass of the carbon source.
[0101] In some specific embodiments of the present invention, the mass content of carboxyl groups in the carboxyl-containing carbon source is 0.3%, 0.5%, 3%, 10%, 15%, 20%, 30%, 50%, 70% or 80%.
[0102] The mass content of carboxyl groups in the carboxyl-containing carbon source in the present invention can be quantitatively determined according to the Boehm titration method in standard GB / T 38114-2019.
[0103] In some specific embodiments of the present invention, the carbon source containing carboxyl zinc coordination bonds is one or more of zinc carboxylate, carbon nanotubes containing carboxyl zinc coordination bonds, and graphite oxide containing carboxyl zinc coordination bonds.
[0104] The carbon nanotubes containing carboxyl zinc coordination bonds in the present invention can be prepared by the Hummers method.
[0105] The graphite oxide containing carboxyl zinc coordination bonds in the present invention can be prepared by the Hummers method.
[0106] The oxidant used in the preparation by the Hummers method can be conventional in the art, such as NaNO3 and KMnO4.
[0107] In some specific embodiments of the present invention, the carbon source containing carboxyl zinc coordination bonds is obtained by reacting a carboxyl-containing carbon source and a zinc source.
[0108] In some specific embodiments of the present invention, the heating rate in the heating stage of calcination is 0.5-2°C / min.
[0109] In some specific embodiments of the present invention, the heating rate in the heating stage of calcination is 0.2°C / min, 0.5°C / min, 1°C / min, 2°C / min or 2.5°C / min.
[0110] In some specific embodiments of the present invention, the temperature of the calcination insulation stage is 250-400°C.
[0111] In some specific embodiments of the present invention, the temperature of the insulation stage of calcination is 200°C, 250°C, 300°C or 500°C.
[0112] In some specific embodiments of the present invention, the holding period of the calcination is 2-4 hours.
[0113] In a specific embodiment of the present invention, the time of the heat preservation stage of calcination is 3 hours.
[0114] Electrochemical Devices
[0115] In the electrochemical device described in the second aspect of the present invention, the negative electrode sheet of the electrochemical device includes the zinc selenide composite carbon material as described above.
[0116] In the present invention, the type of the electrochemical device may be a conventional electrochemical device in the art, such as a sodium ion battery or a lithium ion battery, preferably a sodium ion battery.
[0117] In some specific embodiments of the present invention, the type of the electrochemical device is a sodium ion battery.
[0118] The sodium ion battery generally includes a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte.
[0119] In some optional embodiments, the preparation process of the negative electrode sheet can adopt conventional processes in the art. For example, the following method can be adopted: after the zinc selenide composite carbon material, binder, thickener and conductive agent are mixed in a certain mass ratio, a solvent is added and mixed evenly to obtain a negative electrode slurry; then the negative electrode slurry is evenly coated on the negative electrode current collector to obtain a negative electrode material layer; and then the negative electrode sheet is prepared through drying, cold pressing, slitting and other processes.
[0120] In some optional embodiments, the negative electrode sheet can be prepared by conventional methods in the art. For example, the following method can be used: after the zinc selenide composite carbon material, thickener and conductive agent are mixed in a certain mass ratio, a solvent is added and mixed evenly to obtain a negative electrode slurry; then the negative electrode slurry is evenly coated on the negative electrode current collector to obtain a negative electrode material layer; and then the negative electrode sheet is prepared through drying, cold pressing, slitting and other processes.
[0121] In some specific embodiments, the mass ratio of the zinc selenide composite carbon material, the thickener sodium carboxymethyl cellulose and the conductive agent Super P is 70:15:15.
[0122] In some specific embodiments, the negative electrode current collector may be a current collector conventionally used for the negative electrode in the art, and may be a common current collector or a composite current collector. The negative electrode current collector may use a material that does not cause chemical changes and has conductivity without restriction. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon or aluminum-cadmium alloy, or copper, stainless steel material or aluminum-cadmium alloy surface-treated with carbon, nickel, titanium or silver may be used. In addition, in order to enhance the adhesion of the negative electrode active material, micro-embossing may be formed on the surface of the negative electrode current collector. The negative electrode current collector may be used in various forms, such as a film, sheet, foil, mesh or porous body.
[0123] In some optional embodiments, the thickness of the negative electrode current collector may be 5-10 μm.
[0124] In some specific embodiments, the negative electrode current collector is a copper foil with a thickness of 8 μm.
[0125] Positive electrode
[0126] In some optional embodiments, the positive electrode sheet includes a current collector layer and a positive electrode material layer located on the current collector layer, wherein the positive electrode material layer includes a positive electrode active material and may further include one or more of a binder, a conductive agent and a thickener as required.
[0127] For the positive electrode current collector, materials that do not cause chemical changes and have high conductivity can be used without restriction according to the actual needs of the electrochemical device. For example, stainless steel, aluminum, nickel, titanium or calcined carbon can be generally used, or aluminum or stainless steel materials that have been surface-treated with carbon, nickel, titanium, silver, etc. In order to enhance the adhesion of the positive electrode material layer, micro-embossing can be formed on the surface of the positive electrode current collector. The positive electrode current collector can be used in various forms, such as a film, a sheet, a foil, a mesh or a porous body.
[0128] The positive electrode active material may be a sodium ion material such as a layered oxide, a polyanionic compound, or a Prussian blue / white compound.
[0129] Optionally, the general formula of the layered oxide is Na x [MFeMn]O2, M is selected from at least one of Cu, Ni, Li, Mg, Al, Zn, Ti, Zr and Sn, and x≤1.
[0130] Optionally, the general formula of the polyanionic compound is NaxMy(AaOb)zZw, wherein M is selected from one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Ca, Mg, Al and Nb; A is selected from one or more of Si, S, P, As, B, Mo, W and Ge, and Z is selected from F and / or O.
[0131] Optionally, the general formula of the Prussian blue / white compound is Na x M1[M2(CN)6], wherein M is selected from one or more of Mn, Ni, Co, Zn, Cu and Fe; optionally, 0<x≤2.
[0132] For the positive electrode, metallic sodium can be used as the reference electrode.
[0133] The conductive agent in the positive electrode material layer can be any conductive agent conventionally used for positive electrodes in the art. For example, the following can be used: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and carbon nanotubes (CNT); metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium dioxide; or conductive polymers, such as polyphenylene derivatives, etc.
[0134] For the binder in the positive electrode material layer, it can be a binder conventionally used for the positive electrode in the art. For example, it can include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one or a mixture of two or more thereof can be used.
[0135] The thickener in the positive electrode material layer may be a thickener conventionally used for positive electrodes in the art. The addition of the thickener may increase the system viscosity of each component in the positive electrode active material layer. Generally, a sodium carboxymethyl cellulose (CMC) solution may be selected.
[0136] In the present invention, the positive electrode sheet can be prepared by conventional methods in the art. For example, the following method can be used: after the positive electrode active material, the conductive agent, the thickener and the binder are mixed in a certain mass ratio, a solvent is added and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector; and then the positive electrode sheet is prepared through processes such as drying, rolling, and cutting.
[0137] Diaphragm
[0138] In some optional embodiments, the separator can be made of polypropylene film, polyethylene film or glass fiber film.
[0139] Wherein, the air permeability of the diaphragm may be 180-380s / 100mL.
[0140] Wherein, the porosity of the diaphragm may be 30%-50%.
[0141] Wherein, the thickness of the diaphragm may be 9-18 μm.
[0142] Electrolyte
[0143] In some embodiments, the electrolyte may be an electrolyte conventionally used for batteries in the art, generally including a non-aqueous solvent, a sodium salt, and an additive.
[0144] Wherein, the non-aqueous solvent can be a conventional non-aqueous solvent in the art, preferably an ester solvent, and more preferably a carbonate solvent. The carbonate solvent can be selected from one or more of dimethyl carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).
[0145] Among them, the additive can be selected from one or more of vinylene carbonate (VC), dimethyl fluorocarbonate (FEC), vinyl ethylene carbonate (VEC), diethylene sulfate (DTD), vinylene sulfate, 1,3-propane sultone (PS), allyl sultone and 1,4-butane sultone.
[0146] The sodium salt may be a conventional sodium salt in the art, such as NaCF3SO3.
[0147] Wherein, the volume ratio of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate is preferably 1:1:1.
[0148] In a specific embodiment, the electrolyte includes sodium trifluoromethanesulfonate (NaCF3SO3) and diethylene glycol dimethyl ether (DEGDME).
[0149] In some embodiments, the method for preparing the sodium ion battery preferably includes the following steps: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, so that the separator is located between the positive and negative electrode sheets to play an isolating role. Then wrapping with an aluminum plastic film, injecting the above-prepared electrolyte after drying, and finally preparing a soft-pack battery with a capacity of 1Ah after packaging, standing, and forming.
[0150] In some other specific embodiments of the present invention, the electrochemical device is a lithium ion battery.
[0151] The lithium sodium ion battery generally includes a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte.
[0152] In some optional embodiments, the preparation process of the negative electrode sheet can adopt conventional processes in the art. For example, the following method can be adopted: after the zinc selenide composite carbon material, binder, thickener and conductive agent are mixed in a certain mass ratio, a solvent is added and mixed evenly to obtain a negative electrode slurry; then the negative electrode slurry is evenly coated on the negative electrode current collector to obtain a negative electrode material layer; and then the negative electrode sheet is prepared through drying, cold pressing, slitting and other processes.
[0153] In some optional embodiments, the negative electrode sheet can be prepared by conventional methods in the art. For example, the following method can be used: after the zinc selenide composite carbon material, thickener and conductive agent are mixed in a certain mass ratio, a solvent is added and mixed evenly to obtain a negative electrode slurry; then the negative electrode slurry is evenly coated on the negative electrode current collector to obtain a negative electrode material layer; and then the negative electrode sheet is prepared through drying, cold pressing, slitting and other processes.
[0154] In some specific embodiments, the negative electrode current collector may be a current collector conventionally used for the negative electrode in the art, and may be a common current collector or a composite current collector. The negative electrode current collector may use a material that does not cause chemical changes and has conductivity without restriction. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon or aluminum-cadmium alloy, or copper, stainless steel material or aluminum-cadmium alloy surface-treated with carbon, nickel, titanium or silver may be used. In addition, in order to enhance the adhesion of the negative electrode active material, micro-embossing may be formed on the surface of the negative electrode current collector. The negative electrode current collector may be used in various forms, such as a film, sheet, foil, mesh or porous body.
[0155] In some optional embodiments, the thickness of the negative electrode current collector may be 5-10 μm.
[0156] In some specific embodiments, the negative electrode current collector is a copper foil with a thickness of 8 μm.
[0157] Positive electrode
[0158] In some optional embodiments, the positive electrode sheet includes a current collector layer and a positive electrode material layer located on the current collector layer, wherein the positive electrode material layer includes a positive electrode active material and may further include one or more of a binder, a conductive agent and a thickener as required.
[0159] For the positive electrode current collector, materials that do not cause chemical changes and have high conductivity can be used without restriction according to the actual needs of the electrochemical device. For example, stainless steel, aluminum, nickel, titanium or calcined carbon can be generally used, or aluminum or stainless steel materials that have been surface-treated with carbon, nickel, titanium, silver, etc. In order to enhance the adhesion of the positive electrode material layer, micro-embossing can be formed on the surface of the positive electrode current collector. The positive electrode current collector can be used in various forms, such as a film, a sheet, a foil, a mesh or a porous body.
[0160] The positive electrode active material may be a positive electrode active material conventionally used for positive electrodes of lithium ion batteries in the art, such as LiFePO4 or NCM811 ternary positive electrode materials.
[0161] The conductive agent in the positive electrode material layer can be any conductive agent conventionally used for positive electrodes in the art. For example, the following can be used: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and carbon nanotubes (CNT); metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium dioxide; or conductive polymers, such as polyphenylene derivatives, etc.
[0162] For the binder in the positive electrode material layer, it can be a binder conventionally used for the positive electrode in the art. For example, it can include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one or a mixture of two or more thereof can be used.
[0163] The thickener in the positive electrode material layer may be a thickener conventionally used for positive electrodes in the art. The addition of the thickener may increase the system viscosity of each component in the positive electrode active material layer. Generally, a sodium carboxymethyl cellulose (CMC) solution may be selected.
[0164] In the present invention, the positive electrode sheet can be prepared by conventional methods in the art. For example, the following method can be used: after the positive electrode active material, the conductive agent, the thickener and the binder are mixed in a certain mass ratio, a solvent is added and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector; and then the positive electrode sheet is prepared through processes such as drying, rolling, and cutting.
[0165] Diaphragm
[0166] In some optional embodiments, the separator can be made of polypropylene film, polyethylene film or glass fiber film.
[0167] Wherein, the air permeability of the diaphragm may be 180-380s / 100mL.
[0168] Wherein, the porosity of the diaphragm may be 30%-50%.
[0169] Wherein, the thickness of the diaphragm may be 9-18 μm.
[0170] Electrolyte
[0171] In some embodiments, the electrolyte may be an electrolyte conventionally used for batteries in the art, generally including a non-aqueous solvent, a lithium salt, and additives.
[0172] Wherein, the non-aqueous solvent can be a conventional non-aqueous solvent in the art, preferably an ester solvent, and more preferably a carbonate solvent. The carbonate solvent can be selected from one or more of dimethyl carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).
[0173] Among them, the additive can be selected from one or more of vinylene carbonate (VC), dimethyl fluorocarbonate (FEC), vinyl ethylene carbonate (VEC), diethylene sulfate (DTD), vinylene sulfate, 1,3-propane sultone (PS), allyl sultone and 1,4-butane sultone.
[0174] The lithium salt may be a conventional lithium salt in the art, such as LiPF6.
[0175] Wherein, the concentration of the lithium salt may be 1 mol / L.
[0176] In a specific embodiment, the electrolyte includes LiPF6, ethylene carbonate, ethyl methyl carbonate and diethyl carbonate.
[0177] In some embodiments, the electrolyte can be prepared by conventional methods in the art. Optionally, it can be prepared by the following method: ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0178] In some embodiments, the preparation method of the lithium-ion battery preferably includes the following steps: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, so that the separator is located between the positive and negative electrode sheets to play an isolating role. Then wrapping with aluminum plastic film, injecting the above-prepared electrolyte after drying, and finally preparing a soft-pack battery with a capacity of 1Ah after packaging, standing, and forming.
[0179] Electronic devices
[0180] The electronic device provided in the third aspect of the present invention comprises the electrochemical device as described above.
[0181] Exemplarily, the electronic device described in the present invention may be, but is not limited to, mobile devices (such as mobile phones, tablet computers, laptop computers, video recorders, portable printers / copiers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems and backup power supplies, etc.
[0182] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0183] The reagents and raw materials used in the present invention are commercially available.
[0184] Embodiment 1-35
[0185] The preparation of the zinc selenide composite carbon material of Example 1 is carried out according to the following steps:
[0186] Selenium source elemental selenium, zinc source zinc nitrate and carboxyl-containing carbon source citric acid are placed in a small porcelain boat and calcined in a tubular furnace in an atmosphere containing H2 and argon to obtain a zinc selenide composite carbon material; the mass ratio of zinc nitrate, citric acid and elemental selenium is 2:1:2; in the atmosphere containing H2 and argon, the volume concentration of H2 is 5%; the mass content of carboxyl in citric acid is 70%; the heating rate of calcination is 1°C / min, the temperature of the calcination insulation stage is 300°C, and the time of the calcination insulation stage is 3h. The specific parameters of Example 1 are listed in Table 1.
[0187] The preparation of the zinc selenide composite carbon material of Example 2-34 follows the same steps as Example 1, and the time of the calcination insulation stage is 3 hours. Except for the parameters listed in Table 1, other conditions are the same as Example 1. Other specific parameters are listed in Table 1.
[0188] The preparation of the zinc selenide composite carbon material of Example 35 is carried out according to the following steps:
[0189] The zinc source zinc nitrate and the carboxyl-containing carbon source citric acid are mixed to prepare a carbon source containing carboxyl zinc coordination bonds, that is, the carbon source contains coordination bonds between carboxyl groups and zinc ions, and then the selenium source elemental selenium and the carbon source containing carboxyl zinc coordination bonds are placed in a small porcelain boat and calcined in a tube furnace under an atmosphere containing H2; the specific parameters are listed in Table 1. The schematic diagram of the preparation steps of the zinc selenide composite carbon material of Example 35 is shown in Fig.29As shown, specifically, a zinc source zinc nitrate and a carboxyl-containing carbon source citric acid (Citric Acid) are mixed to prepare a carbon source (Zinc Citrate) containing a carboxyl zinc coordination bond, that is, the carbon source contains a coordination bond between a carboxylate and a zinc ion, and then a selenium source elemental selenium (Se) and a carbon source containing a carboxyl zinc coordination bond are placed in a small porcelain boat and calcined in a tubular furnace in an atmosphere containing H2.
[0190] Among them, the carboxylated carbon nanotubes used in Example 2 are conventional commercially available carbon nanotubes. NaNO3 and KMnO4 are used as oxidants, and the carboxylated carbon nanotubes are prepared by the Hummers method, so that part of the carbon in the carbon nanotubes is oxidized to obtain carboxyl groups and hydroxyl groups, so that the mass content of carboxyl groups in the carbon nanotubes is 20%.
[0191] The graphite oxide used in Example 3 is conventional commercially available graphite. NaNO3 and KMnO4 are used as oxidants, and the graphite oxide is prepared by the Hummers method, so that part of the carbon in the graphite is oxidized to obtain carboxyl groups and hydroxyl groups, so that the mass content of carboxyl groups in the graphite is 15%.
[0192] The cyclohexane tetracarboxylic acid used in Example 17 is cyclohexane-1,2,4,5-tetracarboxylic acid, and its molecular formula is C 10 H 12 O8, molecular weight is 260.2.
[0193] Wherein, the myristic acid molecular formula used in Example 20 is C 14 H 28 O2, molecular weight is 228.37.
[0194] Comparative Example 1
[0195] Comparative Example 1 uses pure phase zinc selenide, and its preparation method is as follows: zinc nitrate and elemental selenium powder are mixed in a mass ratio of 1:1 and fully ground for 1 hour, and placed in a small porcelain boat, and calcined in an atmosphere containing H2 and argon in a tubular furnace to obtain pure phase zinc selenide; in the atmosphere containing H2 and argon, the volume concentration of H2 is 5%; the heating rate of calcination is 1°C / min, the temperature of the calcination insulation stage is 300°C, and the time of the calcination insulation stage is 3h.
[0196] Comparative Example 2
[0197] The carbon source used in Comparative Example 2 is 2-methylimidazole, which does not contain a carboxyl group. Other conditions are the same as those in Example 1. Other specific parameters are listed in Table 1.
[0198] Comparative Example 3
[0199] The carbon source used in Comparative Example 3 is 1-methylpyrrole, which does not contain a carboxyl group. Other conditions are the same as those in Example 1. Other specific parameters are listed in Table 1.
[0200] Table 1
[0201]
[0202]
[0203]
[0204] The zinc selenide composite carbon material prepared in the above-mentioned embodiments 1-35 includes a porous carbon substrate and zinc selenide nanoparticles. The porous carbon substrate and the zinc selenide nanoparticles are connected by Zn-OC bonds to form zinc selenide nanoparticles anchored on the porous carbon substrate, wherein the porous carbon substrate includes amorphous carbon and graphitized carbon.
[0205] The zinc selenide composite carbon materials prepared in Examples 1-35 and the materials in Comparative Examples 2-3 were subjected to the following tests, and the test results are listed in Table 2:
[0206] 1. Determination of porosity, pore volume and average pore size of zinc selenide composite carbon materials: The instrument used is micromeritics ASAP 2460 specific surface area analyzer, and the test method refers to the gas adsorption method in standard GB / T21650.3-2011.
[0207] The specific steps of the gas adsorption method are as follows: first, the zinc selenide composite carbon material sample is heated and vacuumed to remove the impurity gas adsorbed on the surface. Then it is weighed and placed in liquid nitrogen. At the liquid nitrogen temperature, the nitrogen adsorption amount of the sample is measured at different pre-set pressure points to obtain the adsorption isotherm. Then the data is processed to calculate the porosity, pore volume and average pore size from the adsorption isotherm.
[0208] Among them, the particle size D50 of the pure phase zinc selenide in Comparative Example 1 is 38 nm.
[0209] 2. Determination of the specific surface area of zinc selenide composite carbon materials: The instrument used is micromeritics ASAP2460 specific surface area analyzer, and the test method refers to the gas adsorption BET method in the standard GB / T19587-2017.
[0210] 3. Determination of the mass content of porous carbon substrate and zinc selenide nanoparticles in zinc selenide composite carbon material:
[0211] The quality of the porous carbon substrate was measured using a Simultaneous DSC-TGA QSeries instrument - SDT Q600 produced by TA Company of the United States. The test method was thermogravimetry. The test conditions were: argon atmosphere, room temperature (20°C)-800°C, and a heating rate of 10°C / min.
[0212] Calculation of the mass content of the porous carbon substrate in the zinc selenide composite carbon material: mass of the porous carbon substrate / mass of the zinc selenide composite carbon material;
[0213] Calculation of the mass content of zinc selenide nanoparticles in the zinc selenide-carbon composite material: (mass of zinc selenide-carbon composite material-mass of porous carbon substrate) / mass of zinc selenide-carbon composite material.
[0214] 4. Determination of the mass content of oxygen in zinc selenide composite carbon materials: The instrument used is a high-precision titrator, and the test method refers to the Boehm titration method in the standard GB / T 38114-2019. The specific steps are: take a certain volume of NaHCO3 solution of known concentration to soak a certain amount of zinc selenide composite carbon material, react for 20 hours under magnetic stirring, then filter, measure a certain volume of filtrate, and titrate the filtrate with a hydrochloric acid solution of known concentration to obtain the concentration of NaHCO3 in the filtrate. According to the change in the concentration of NaHCO3 solution before and after the reaction and the volume of NaHCO3 solution used to soak the test material, the amount of NaHCO3 that reacts with the carboxyl group on the surface of the material is obtained, and finally the absolute mass percentage of the carboxyl group on the surface of the material is calculated.
[0215] Table 2
[0216]
[0217]
[0218] The nitrogen adsorption / desorption isotherm curve of the zinc selenide composite carbon material of Example 1 is as follows Figure 1 The pore size distribution diagram is shown in Figure 2 As shown, its TG / DTA diagram is as follows Figure 3 As shown, Figure 2 It shows that the zinc selenide composite carbon material of Example 1 has mesopores and macropores, and the mesopores account for a relatively high proportion.
[0219] The SEM images of the zinc selenide composite carbon material of Example 1 magnified 2000 times, 5000 times and 10000 times are as follows: Figure 4 , Figure 5 , Figure 6 shown.
[0220] The mapping image of the zinc selenide composite carbon material of Example 1 is as follows Figure 7 As shown, it is obtained by surface scanning mapping analysis using an EDS spectrometer.
[0221] The TEM image, HRTEM image and SAED image of the zinc selenide composite carbon material of Example 1 are shown as follows: Figure 8 , Fig. 9 and Fig.10 shown.
[0222] The XRD spectra of the zinc selenide composite carbon material (ZnSe / C) of Example 1, the zinc selenide (pure ZnSe) and the pure carbon (Carban) of Comparative Example 1 are shown in FIG. Fig.11 As shown, the Raman spectrum of Example 1 is as shown Fig.12 shown.
[0223] The infrared spectra of the zinc selenide composite carbon material (ZnSe / C) of Example 1, the zinc selenide (ZnSe), pure carbon (Carban) and zinc acetylacetonate (Zine acetylacetonate) of Comparative Example 1 are shown in FIG. Fig.13 shown.
[0224] The full XPS spectrum of the zinc selenide composite carbon material of Example 1, the high-resolution spectrum of C 1s, the high-resolution spectrum of O 1s, the high-resolution spectrum of Zn 2p, and the high-resolution spectrum of Se 3d are shown respectively. Fig.14 , Fig.15 , Fig.16 , Fig.17 , Fig.18 shown.
[0225] Among them, according to Fig.13 As a result, zinc acetylacetonate was detected at 500 cm -1 The absorption peak at corresponds to the Zn-OC bond. At the same time, this peak is also found in the zinc selenide composite carbon material of Example 1, indicating that there is a Zn-OC bond in the zinc selenide composite carbon material. Fig.15 The results show that the characteristic peak at 286.35 eV proves the existence of Zn-OC bond in ZnSe composite carbon materials. Fig.16 The results also proved the existence of Zn-OC bond at 533.03 eV.
[0226] Effect Example 1
[0227] (1) Preparation of sodium ion batteries
[0228] ① Preparation of negative electrode
[0229] The zinc selenide composite carbon material prepared in the above examples and comparative examples was used as the negative electrode active material to prepare the negative electrode sheet, and 70wt% of the negative electrode active material, 15wt% of Super P and 15wt% of sodium carboxymethyl cellulose (CMC) were uniformly mixed with deionized water as a solvent. The uniform slurry was then coated on a copper foil, vacuum dried at 60°C for 12 hours, and then cut into discs with a diameter of 10mm to obtain a negative electrode sheet.
[0230] ② Preparation of reference electrode
[0231] Metallic sodium was used as the reference electrode.
[0232] ③ Preparation of electrolyte
[0233] A 1 M sodium trifluoromethanesulfonate (NaCF3SO3) solution in diethylene glycol dimethyl ether (DEGDME) was used as the electrolyte.
[0234] ④ Preparation of diaphragm
[0235] A glass fiber membrane is used as the diaphragm, the thickness of the diaphragm is 12 μm, the air permeability is 230 s / 100 mL, and the porosity is 40%.
[0236] Assembly of sodium-ion half-cell: In a glove box filled with helium, the composite negative electrode material, separator, and sodium sheet are stacked into the positive electrode shell of the button battery in sequence, and then the electrolyte is injected using a pipette. Finally, the negative electrode cover is assembled and the battery is locked using a punch to complete the assembly of the button half-cell (CR2032).
[0237] (2) The sodium ion half-cell is tested as follows:
[0238] Before the test, the battery was activated for 3 cycles at a current density of 0.1A / g and a voltage range of 0.1-3.0V (i.e., the discharge cut-off voltage was 0.1V and the charge cut-off voltage was 3.0V). The discharge capacity of the third activation cycle was taken as the initial discharge capacity of the battery. The following tests were then performed (the voltage range of each test was 0.1-3.0V);
[0239] 1. Discharge capacity test after 500 cycles at 0.5 A / g: At 25°C, after 500 cycles of charge and discharge at a current density of 0.5 A / g, record the charge and discharge capacity of the 500th cycle.
[0240] 2. Discharge specific capacity test after 1000 cycles at 5A / g: After 1000 cycles of charge and discharge at a current density of 5A / g at 25°C, record the charge and discharge specific capacity of the 1000th cycle.
[0241] In each test, 5 newly prepared button half-cells (parallel samples) were taken from the comparative examples and embodiments, the data of the parallel samples in each comparative example and embodiment were recorded, and the average value was taken as the test data.
[0242] The above test methods are conventional test methods in the art, and more specific details are not repeated here.
[0243] The above test results are listed in Table 3:
[0244] Table 3
[0245]
[0246]
[0247] The capacities of Example 1 at current densities of 0.2A / g, 0.5A / g, 1A / g, 2A / g, 2.5A / g, and 5A / g are 426.6mAhg -1 、381mAhg -1 、357mAhg -1 、316.3mAhg -1 、298.5mAhg -1 、281.1mAhg -1 The electrochemical performance of Example 35 is comparable to that of Example 1.
[0248] The TEM image, HRTEM image and SAED image of the zinc selenide composite carbon material prepared in Example 1 after the battery was cycled 500 times are as follows: Fig.19 , Fig. 20 and Fig.21 shown.
[0249] The non-in-situ XRD patterns of the zinc selenide composite carbon material of Example 1 at different charge and discharge pressures and the corresponding charge and discharge curves are shown in Figures 1 and 2. Fig. 22 and Fig.23 shown.
[0250] The cycle performance of the zinc selenide composite carbon material (ZnSe / C) of Example 1, the zinc selenide (Bulk ZnSe) of Comparative Example 1 and pure carbon (Carban) is shown in the figure. Fig.24 shown.
[0251] The constant current discharge / charge curve of the zinc selenide composite carbon material (ZnSe / C) of Example 1 at 0.5A / g is as follows: Fig.25 shown.
[0252] The rated capacity of the zinc selenide composite carbon material (ZnSe / C) of Example 1 and the zinc selenide (pure ZnSe) of Comparative Example 1 at different current densities is shown in the figure below: Fig.26 shown.
[0253] The discharge / charge platform diagram of the zinc selenide composite carbon material (ZnSe / C) of Example 1 is shown in FIG. Fig. 27 shown.
[0254] The schematic diagram of the long cycle stability of the zinc selenide composite carbon material (ZnSe / C) of Example 1 at a high current density of 5A / g is shown in FIG. Fig.28 shown.
[0255] When the zinc selenide composite carbon material prepared in the embodiment of the present invention is used in a battery, the discharge specific capacity after cycling for 500cls at 0.5A / g can reach 311mAhg -1The above results show that the discharge capacity after 1000 cls cycling at 5A / g can reach 197 mAhg -1 Above, the capacity can reach 337mAhg at 0.1A / g -1 The above indicates that the zinc selenide composite carbon material prepared by the present invention can have excellent cycle performance and rate performance when used in batteries.
[0256] Compared with Example 1, the selenium source and the zinc source are not compounded with the carbon source containing carboxyl groups, and the prepared pure phase zinc selenide has a discharge capacity of only 187 mAh g after cycling for 500 cls at 0.5 A / g. -1 The discharge capacity after 1000 cls cycling at 5A / g is only 114 mAhg -1 , indicating that the cycle performance of Comparative Example 1 is worse than that of the embodiment.
[0257] Compared with Example 1, in Comparative Example 2, only citric acid is replaced by 2-methylimidazole, which does not contain a carboxyl group. Compared with Example 1, the discharge capacity of Comparative Example 2 after cycling for 500cls at 0.5A / g is increased from 434mAhg -1 Reduced to 335mAhg -1 , the discharge capacity after 1000cls cycling at 5A / g increased from 285mAhg -1 Reduced to 177mAhg -1 , the capacity at 0.1A / g increased from 480.5mAhg -1 Reduced to 374mAhg -1 , indicating that the comparative example 1 uses 2-methylimidazole without a carboxyl group, which significantly reduces the cycle performance and rate performance of the battery.
[0258] Compared with Example 1, Comparative Example 3 only replaces citric acid with 1-methylpyrrole, which does not contain a carboxyl group. Compared with Example 1, the discharge capacity of Comparative Example 2 after cycling for 500cls at 0.5A / g is increased from 434mAhg -1 Reduced to 317mAhg -1 , the discharge capacity after 1000cls cycling at 5A / g increased from 285mAhg -1 Reduced to 145mAhg -1 , the capacity at 0.1A / g increased from 480.5mAhg -1 Reduced to 345mAhg -1 , indicating that Comparative Example 2 uses 1-methylpyrrole without a carboxyl group, which significantly reduces the cycle performance and rate performance of the battery.
[0259] According to the results of Examples 1, 12 to 15, if the volume concentration of H2 in the atmosphere is 5% to 20%, the discharge capacity after 500 cls cycling at 0.5 A / g can reach 395 mAh g. -1 The above results show that the discharge capacity after 1000 cls cycling at 5A / g can reach 249 mAhg -1 Above, the capacity can reach 430mAhg at 0.1A / g -1 The above further improves the cycle performance and rate performance of the battery.
[0260] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A zinc selenide composite carbon material, characterized in that: The invention comprises a porous carbon substrate and zinc selenide nanoparticles. The porous carbon substrate and the zinc selenide nanoparticles are connected via Zn-OC bonds to form the zinc selenide nanoparticles anchored on the porous carbon substrate.
2. The zinc selenide composite carbon material according to claim 1, characterized in that: The zinc selenide composite carbon material satisfies one or more of the following conditions (a)-(e): (a) The porosity of the zinc selenide composite carbon material is 20%-45%; (b) The pore volume of the zinc selenide composite carbon material is 0.001-0.02cm 3 / g; (c) the average pore size of the zinc selenide composite carbon material is 30-50 nm; (d) The specific surface area of the zinc selenide composite carbon material is 5-10m 2 / g; (e) The particle size D50 of the zinc selenide nanoparticles is ≤100 nm.
3. The zinc selenide composite carbon material according to claim 1, characterized in that: The zinc selenide composite carbon material satisfies one or two of the following conditions (a)-(b): (a) the porous carbon substrate accounts for 15%-40% of the mass of the zinc selenide composite carbon material; (b) The mass content of the zinc selenide nanoparticles in the zinc selenide composite carbon material is 60%-85%.
4. The zinc selenide composite carbon material according to claim 1, characterized in that: The zinc selenide composite carbon material satisfies one or more of the following conditions (a)-(c): (a) the porous carbon substrate comprises amorphous carbon; (b) the particle size D50 of the zinc selenide nanoparticles is 10-40 nm; (c) The mass content of oxygen in the zinc selenide composite carbon material is 5%-20%.
5. The zinc selenide composite carbon material according to any one of claims 1 to 4, characterized in that: The preparation method of the zinc selenide composite carbon material comprises the following steps: calcining the raw material mixture in an atmosphere containing H2; Wherein, the raw material mixture comprises a selenium source, a zinc source and a carbon source containing a carboxyl group; or, the raw material mixture comprises a selenium source and a carbon source containing a carboxyl zinc coordination bond.
6. The zinc selenide composite carbon material according to claim 5, characterized in that: The preparation method of the zinc selenide composite carbon material meets one or more of the following conditions (a)-(f): (a) the carboxyl-containing carbon source is one or more of carboxylic acid, carboxylated carbon nanotubes and graphite oxide; (b) the zinc source is zinc nitrate; (c) the selenium source is elemental selenium; (d) the mass ratio of the zinc source, the carboxyl-containing carbon source and the selenium source is (1.5-2.5):1:(1.5-2.5); (e) In the atmosphere containing H2, the volume concentration of H2 is 5%-20%; (f) The mass content of carboxyl groups in the carboxyl-containing carbon source is 0.5%-70%.
7. The zinc selenide composite carbon material according to claim 5, characterized in that: The carbon source containing carboxyl zinc coordination bonds satisfies one or two of the following conditions (a)-(b): (a) the carbon source containing carboxyl zinc coordination bonds is one or more of zinc carboxylate, carbon nanotubes containing carboxyl zinc coordination bonds, and graphite oxide containing carboxyl zinc coordination bonds; (b) The carbon source containing carboxyl zinc coordination bonds is obtained by reacting a carboxyl-containing carbon source and a zinc source.
8. The zinc selenide composite carbon material according to claim 5, characterized in that: The preparation method of the zinc selenide composite carbon material meets one or more of the following conditions (a)-(c): (a) the heating rate of the heating stage of the calcination is 0.5-2°C / min; (b) the temperature of the calcination insulation stage is 250-400° C.; (c) The time of the calcination heat preservation stage is 2-4h.
9. An electrochemical device, characterized in that: The negative electrode sheet of the electrochemical device comprises the zinc selenide composite carbon material according to any one of claims 1 to 8.
10. An electronic device comprising the electrochemical device according to claim 9.
Citation Information
Patent Citations
Preparation method of double-carbon modified zinc selenide layered multistage microspheres
CN113912026A